Efektivitas Pembelajaran Kooperatif Tipe STAD Pada Materi Pokok Perbandingan Di SMPN II Megaluh Jombang - Rifa Nurmilah (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
The aims of this research are: 1) to investigate the effectiveness of cooperative teaching practice using STAD type in the topic of comparison; 2). investigate whether the learning outcome of the students who were involved in cooperative learning process is better than those who were involved in conventional learning process in the topic of comparison. This research was quasi experimental research. The samples of this research were the students of VIIA as the experimental classroom and the students of VIIB as the control classroom. Based on the descriptive analysis, it was concluded that the use of cooperative learning using STAD type in the topic of comparison in SMPN II Megaluh was proven effective with criteria 1) students mastery reach 87.09%, 2) the students active participation is effective, 3) the teachers capability in managing classroom is effective, 4) the students response of the teaching and learning practice are positive. Based on the analysis by using inferential t-test, it was gained ttest= 2.197 and ttest > ttable,. It means the students learning outcome using cooperative teaching and learning process was better than those using conventional teaching and learning process in SMPN II Megaluh Jombang, academic year 2013/2014.